Reinterpretation Of Istanbul’s Image Through Light Mapping - Kutlu, Rana; Manav, Banu (The Turkish Online Journal of Design, Art and Communication, 2012)
In the present study, historical and contemporary masterpieces in Istanbul will be discussed and analyzed considering “lighting scheme” as a design tool in the “lighting master plan”. The present image of the city will be analyzed together with the light mapping tool. It was intended to introduce a “conceptual lighting master plan” where a lighting vocabulary is introduced for both educational purpose and as a metaphor in line with the enormous historical background of Istanbul. The scheme can be an overview or road map of how lighting might be used to meet the various program requirements while it also enhances and entegrates with the architecture.Through the effective use of the lighting scheme, the unityand diversity in the history of the old city can be highlighted.
Keywords: Light Mapping; Visual Culture; Işık Haritalama; Görsel Kültür